Valorificarea gândirii filosofico-politice a lui Constantin Stere în Republica Moldova [Articol] - Jacota-Dragan, Olga (USARB, 2016)
Literary and social-policy work of Stere was intentionally omitted in Republic of Moldova by the end of the XX-th century, but to do well, censorship of political regime was weak and powerless against the desire of Stere’s work. Local researchers pay particular attention to the place and role of Stere in initiating new current ideas as populism and peasantism. Development of programs and ideologies of government as Liberal National Party (1900), the National Peasant Party (1926) and his work in founding and leadership of magazine „Cottage Life” (1906), also interest for researchers from Moldova. His personality is returned to our country both through republishing work and through interpretation.
Keywords: Stere Constantin (1865-1936); gândire filosofică; gândire politică